The contract with God trilogy life on Dropsie Avenue - Eisner, Will 1917-2005 (W.W. Norton & Company, 2006)
The legendary graphic novel and the sequels that launched an art form. With graphic narrative that "was closer to the writing of Bernard Malamud or Isaac Bashevis Singer than any comic art which had preceded it" (The Economist), A Contract with God, originally published in 1978, was the first graphic novel: the prototype-along with A Life Force and Dropsie Avenue-for such seminal works as Maus and Persepolis. Set during the Great Depression, this literary trilogy, assembled in one volume for the first time, presents a treasure house of now near-mythic stories that fictionally illustrate the bittersweet tenement life of Eisner's youth. With nearly one dozen new illustrations and a revealing brand-new foreword, this book ultimately tells the epic story of life, death, and resurrection while exploring man's fractious relationship with an all-too-vengeful God. This mesmerizing, fictional chronicle of the universal American immigrant experience is Eisner's most poignant and enduring legacy.
Keywords: Eisner, Will -- 1917-2005; Einwanderer; Immigrants -- New York (State) -- New York -- Comic books, strips, etc; Tenement houses -- New York (State) -- New York -- Comic books, strips, etc; Mietshaus; Graphic Novel; New York, NY; Graphic novels; Comic